Identification of Lead and Cadmium Contaminants in Borehole Water in Tamangapa Village - Idris, Hazizah; Syamsul, Muharti; Aswadi, Aswadi; Wijaya, Ivan (Universitas Islam Negeri Alauddin Makassar, 2025)
The process of gradually stockpiling waste in landfill areas can produce problems in the form of leachate that can seep into the soil and rivers, which can cause a decrease in groundwater quality. The type of research used in quantitative research with observational descriptive method. The three borehole water samples taken from the research site contained cadmium and lead. The results of cadmium levels obtained (0.00001 mg/L) meet the requirements for clean water quality according to PERMENKES No. 416 of 1990 (0.005 mg/L), while lead levels in the first and second samples meet the requirements for clean water quality (<0.05 mg/L), while in the third sample, the lead level obtained was 0.0527 mg/L, which exceeds the amount required for clean water quality (0.05 mg/L). Keywords: Pollution, Lead, Cadmium, Borehole Water, Tamangapa